STUDIES ON HIDARI IRAVA LEAF CONSUMPTION IN RELATION TO WARNING SYSTEM IN THE CONTROL OF THE COCONUT PEST - Wily A. Baringbing; Bariyah Baringbing (International Coconut Community, 1993)
Two‑month laboratory and field experiments were carried out to investigate amount of leaflet consumed by the leaf‑eating caterpillar. Hidari irava Moore, during the larval stadium in an effort to determine the right time to control the pest chemically. The experiment was conducted in Pakuwon Experimental Garden, West Java, Indonesia in 1990. A total of 70 larvae of the hesperiid were reared in laboratory. Mature coconut leaflets replaced daily with fresh material. Were cut arid measured for food of the caterpillars in glass containers. Fifty mature hybrid coconuts, Malayan Red Dwarf (MRD) x West African Tall (WAT), were studied to calculate the leaflet weight of each leaf. A leaf was cut from each palm. There were 50 leaves used altogether. Results of the study showed that a single larva, from the second to fifth instars, consumed 13.90 g coconut leaflet. Weight of leaflets per leaf was 2,562.79 g and 66,455.29 g per tree. A population of 18.43 larvae per leaf caused 10% damage to the crown of a palm tree.